Automatic characterization of silicon single-photon avalanche photodiode - Aina Mardhiyah Mohamad Ghazali (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
In low intensity photon counter technology, silicon avalanche photodiode (SPAD) is currently the preferred detector. While operating at high reverse voltages known as the Geiger mode, weak incident photons would trigger internal signal amplification which leads to the generation of self-sustaining multiple electron-hole pairs. This characteristic enables the avalanche photodiode to be used as single photon detectors. It offers a low dark count rate, high detection efficiency and a high count rate in the visible to near-infrared range (wavelength below 1000 nm). Silicon APDs as single photon detectors are very sensitive to the choice of operating overbias voltage and temperature. Besides, the type of quenching electronics utilized has an influence on the SPADs characteristics as well. Even individual APDs produced from a single manufacturer need to be assessed prior to its use as the device is highly sensitive. An automated SPAD characterization platform would definitely be beneficial and advantageous as the test procedures are standardized, more reliable and not prone to inconsistencies. Thus, the present dissertation is focused towards the development of an automated characterization platform of the silicon APD. This work precedes with the common, manual characterization of a commercial silicon SPAD (PerkinElmer C30902EH), using a basic passive quenching scheme with a 390 kΩ ballast resistor. The SPADs are characterized according to their breakdown voltage and dark count rate as a function of overbias voltage and operating temperature. The results obtained substantiate the unique characteristics of each single SPAD unit and the highly sensitive dependence of the dark count rate, and other SPAD's parameters as well, on the choice of overbias voltage and operating temperature. These facts necessitate each SPADs to be characterized prior to its use. Often, repeated measurements are often required. Subsequently, an automated characterization platform of Si SPAD is developed. The automated characterization algorithms are implemented in C++ and Octave on the Linux platform. The detector circuit consists of a simple and robust passively-quenched scheme, a high voltage supply, 390 kΩ bias resistor, and a high speed comparator for sensing the avalanche current. Characterization is performed at a temperature of -25 ºC, maintained using a thermo-electric cooler cell. The automated characterization routine has been successfully implemented and able to elucidate the characteristics of the commercial PerkinElmer C30902SH silicon avalanche photodiode, namely, the current-voltage profiles under three illumination levels i.e. darkness, weak illumination (10pW) and medium illumination (10W), and the detector dark count rate, standard detector count rate and detector efficiency as a function of applied bias voltage. The properties observed are in agreement with published results obtained using the customary, manual approach. Finally, the automated characterization platform developed could easily be adapted and expanded for diverse experimental needs.